Hydroxymethylnitrofurazone (NFOH) decreases parasitaemia, parasitism and tissue lesion caused by infection with the Bolivia Trypanosoma cruzi type I strain in Swiss and C57BL/6 mice - Cauê Benito Scarim; Cleverton Roberto de Andrade; Rossana Falcone; Letícia Moreno Ambrozini; Vitor Izidoro Senhorelli; João Aristeu da Rosa; Chung Man Chin (Universidade de São Paulo, 2023)
Abstract The chemical hydroxymethylation of the antimicrobial nitrofurazone leads to the prodrug NFOH, also increases the anti-T. cruzi activities (in vitro and in vivo), as well as showed non-genotoxic (Ames and micronucleus assays). In the present study, we assessed the anti-T. cruzi effect of the NFOH In vivo - in acute Swiss and C57Bl/6 experimental Chagas models. The treatment started at 5 days post-infection during 20 consecutive days (orally, once day, 150mg/kg), and the parasitaemia as well as histopathology analysis were performed. In both experimental murine models, NFOH was able to reduce parasitemia blood avoiding parasitic reactivation, during immunosuppression period (dexamethasone 5mg/kg, 14 days), in 100% of the mice, and decrease tissue parasite nests, demonstrating absence of amastigote forms in all organs (100%) analyzed, data similar to benznidazole (BZN). Therefore, the results shown here pointing to the NFOH as promising compound for further preclinical studies, being a high potential drug to effective and safe chemotherapy to Chagas disease.